2019
DOI: 10.1371/journal.pone.0214596
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal immunization with recombinant outer membrane protein A induces protective immune response against Stenotrophomonas maltophilia infection

Abstract: Stenotrophomonas maltophilia ( S . maltophilia ), a multi-drug resistant opportunistic pathogen, is associated with nosocomial and community-acquired infections. Preventive and therapeutic strategies for such infections are greatly needed. In this study, sequence alignment analysis revealed that Outer membrane protein A (OmpA) was highly conserved among S . maltophilia strains but shared no significant simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In LPS challenged birds, LEfSe highlights the greater differential abundances of several opportunistic pathogens, including Corynebacteriaceae (Corynebacterium), Staphylococcaceae (Staphylococcus), Erysipelotrichaceae, Brevundimonas and Stenotrophomonas. All of them have been documented to be associated with inflammatory infections [66][67][68][69][70]. In the current study, correlation analysis revealed positive associations between Corynebacteriaceae (Corynebacterium) and Staphylococcaceae (Staphylococcus) with ileal TLR4 and/or IL-6 expressions.…”
Section: Tablesupporting
confidence: 55%
“…In LPS challenged birds, LEfSe highlights the greater differential abundances of several opportunistic pathogens, including Corynebacteriaceae (Corynebacterium), Staphylococcaceae (Staphylococcus), Erysipelotrichaceae, Brevundimonas and Stenotrophomonas. All of them have been documented to be associated with inflammatory infections [66][67][68][69][70]. In the current study, correlation analysis revealed positive associations between Corynebacteriaceae (Corynebacterium) and Staphylococcaceae (Staphylococcus) with ileal TLR4 and/or IL-6 expressions.…”
Section: Tablesupporting
confidence: 55%
“…DAPI was purchased from Beyotime Biotechnology. Purified His-tagged recombinant S. maltophilia OmpW (rOmpW) and rabbit anti-rOmpA serum were obtained from the previous study (Xu et al, 2018;Li et al, 2019). Bax (sc-20067), Bcl-xL (sc-136207), cytochrome c (sc-13156), AIF (sc-55519), caspase-3 (sc-7272), PARP (sc-53643), and β-actin (sc-81178) antibodies were purchased from Santa Cruz.…”
Section: Regents and Antibodiesmentioning
confidence: 99%
“…We developed the His-tagged rOmpA in our previous study (Xu et al, 2018;Li et al, 2019). The recombinant plasmid expressing S. maltophilia K279a OmpA was transformed into E. coli BL21, which was cultured and induced by IPTG.…”
Section: Identification Of Recombinant S Maltophilia Ompamentioning
confidence: 99%
See 1 more Smart Citation